Mediating role of entrepreneurial orientation on relationship between transformational leadership, transactional leadership and performance of small and medium enterprises - Che Mohd Zulkifli Che Omar (Tanjong Malim, 2019)
Mediating role of entrepreneurial orientation on relationship between transformational leadership, transactional leadership and performance of small and medium enterprises by Che Mohd Zulkifli Che Omar